Compound effect diamino-2.5-di(4-hydroxyphenyl)-4-oxo-5-thoiureayl-(1,2,4) Oxadizolidine (Oxa).Oxa The biological activity of the laboratory preparation on some isolates Clinicals - عبد علي الحواني اسراء; حميد عيسى عواطف; انيس ماينا بلسم; شبر غالب الموسوي شروق (University of Thi-Qar Journal of Science, 2009)
The antimicrobial activity of the compound Oxazolidine was studied against some clinical isolates by using disc diffusion method . The Oxa. has broad spectrum of biological activity . It was effective against both gram negative and positive . The percentage of susceptibility of the isolates to Oxa. Was 87 % . The isoletes of Escherichia coli , Coagulase Positive Staphylococcus ( COPS) and Klebsiella sp. Were susceptible to Oxa. By 78.94 % , 90.47 % and 75 % respectivily . While the isolates Pseudomonas aeruginosa , Coagulase Negative Staphylococcus (CONS), Streptococcus pyogenes , Proteus sp. , Salmonella sp. ,Enterococcus faecalis were susceptibility to Oxa. With 100 % . From 100 isoletes used in this study only 13 were resistante to the Oxa. compound As follow : 8 isoletes Escherichia coli , 2 Coagulase Positive Staphylococcus and 3 Klebsiella sp.